A Study of Folk Songs Found in Bhojpur Districts (Sahayaatra सहयात्रा, 2025)
This research article entitled " A Study of Folk Songs Found in Bhojpur District" explores the types of folk song, major themes, its importance and impact of modernity on folk Songs. The required data has been collected from all communities and gender as respondents. Mainly, the data has been collected from the field visit through interviews, questionnaires as research tools under primary source and library as secondary sources. Descriptive and analytical methods have been applied to analyze the data. Bhojpur district as study area and folk songs as content have been chosen as study area. It is based on quantitative research design. This study revealed that Balam, Chandi, Selo, Silok, Shyabru, Teek, Deusi-Voilo, Sangini etc. are the major folk songs of Bhojpur District which is connected with human life, nature, environment. These folk's songs reflect the suffering, discrimination, happiness, separation, religious belief of people. The study is important for all readers and policy makers to preserve it for future generations.